Active Labour Market Policy in Indonesia: Reviewing the Employment Policies and Programmes’ Preparation - Rahmatutik, Nela; Laksmono, Bambang Shergi (International Journal Labs, 2023)
Indonesia experienced a significant increase in the labor force with a percentage reaching 69.30% of the total working age population. This condition is a demographic bonus that must be managed by Indonesia. For this reason, the government is trying to improve the investment climate through the Labor Market Flexicurity approach. However, this approach must be balanced with an Active Labor Market Policy that can boost the competitiveness of the Indonesian workforce. The focus of this research is to describe and analyze the development of Active Labor Market Policy in Indonesia. The approach taken in this research is a qualitative approach using a descriptive research type. Data collection techniques were carried out by means of documentation studies, observations, and interviews with 17 people through purposive sampling. The results of the research show that the development of the implementation of the Active Labor Market Policy needs to be supported by a reliable Labor Market Information System. The priority programs for the Active Labor Market in Indonesia include providing government assistance programs, vocational training programs, providing assistance to job seekers to fostering industrial relations and labor inspection. The target group of the Active Labor Market Policy in Indonesia so far has targeted youth, women and persons with disabilities. Meanwhile, the strategy implemented in Indonesia is based on a demand approach, phasing, involving stakeholders and using technology. The implementation of the Active Labor Market Policy in Indonesia still encounters several obstacles, so that it is not enough to say it is optimally active.